Is SARS an 'Event' that Triggers a Force Majeure Clause? - Mario Nigro and Marianne Smith (Law & Governance, 2003)
With respect to the SARS outbreak, it may be possible for parties to suggest that the Ontario government's declaration of an 'emergency' under the Emergency Management Act, R.S.O., 1990, c.E.9 (the "EMA") qualifies as a triggering event in circumstances where a force majeure clause includes an 'emergency' as a triggering event. The EMA defines an emergency as "a situation or an impending situation caused by the forces of nature, an accident, an intentional act or otherwise that constitutes a danger of major proportions to life or property". Canadian case law offers little guidance with respect to the interpretation of a public health emergency in the context of a force majeure clause.